Hubungan Pengetahuan, Sikap Ibu dan Dukungan Keluarga dengan Kurangnya Minat Ibu Bersalin di Fasilitas Kesehatan Wilayah Kerja Puskesmas Sukarami Kecamatan Sungai Rotan Kabupaten Muara Enim - Delli Aridasari; Erma Puspita Sari; Siti Aisyah Hamid; Eka Rahmawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Based on Permenkes No.97 of 2014 Article 14, i.e. paragraph one states that childbirth must be carried out in a health facility. Based on data from the 2019 RI Ministry of Health, South Sumatra Health Office 2019, Riskesdes 2019, South Sumatra Health Office 2019, Muara Enim District Health Office and Sukarami Health Center there are still deliveries that are not carried out in health facilities. Deliveries that are not carried out at a health facility will lead to complications of childbirth, delay in getting services if complications occur and increase the risk of infection.  The purpose of this study was to determine the relationship between knowledge, mother's attitude and family support with the lack of interest of mothers giving birth in health facilities. This study uses an analytical survey with quantitative methods with a cross sectional research design. This research was conducted in August 2021 at the Sukarami Health Center, Sungai Rotan District, Muara Enim Regency, South Sumatra. The population of this study were all mothers giving birth in the work area of the Sukarami Health Center in 2021, amounting to 301 people. The sample used amounted to 75 of the population taken by using the formula for determining the sample. Data analysis used univariate analysis (proportion) and bivariate analysis (chi square test). The results of the analysis showed that knowledge (p value = 0.022), Mother's Attitude (p value = 0.032) and Family Support (p value = 0.018) had a significant relationship with mothers giving birth in health facilities. The conclusion of this study is that there is an influence between knowledge, mother's attitude and family support with the lack of interest of mothers giving birth in health facilities.